Empathetic skills and coping with cancer patients care difficulties among nurses - Marciniak, Anna; Ślusarska, Barbara J.; Nowicki, Grzegorz (Medycyna Paliatywna/Palliative Medicine, 2015)
Introduction : Nurse’s work with a patient in oncological wards entail many determinants of occupational stress connected with specific problems in cancer care. Difficult situation in clinical practice require from health care professionals adequate ways of coping associated with self abilities despite strong emotions – psychological distress, obtained professional experience and skills, especially interpersonal and communication abilities including empathic behaviours. Aim of the study : Determine the level of empathetic skills and coping with difficulties in caring for cancer patients among nurses. Material and methods : The study included 102 nurses randomly chosen, actively working in oncology wards and hospite. The method of diagnostic survey was used. The research tools used in the study were: The original questionnaire, The questionnaire of empathic understanding other people by Węgliński and Scale of Coping by Lazarus and Folkman adapted by Łosiak. Results and conclusions : Nurses caring for patients with cancer are characterized by high level of empathy. The most frequently chosen method to cope with stressful situation was problem orientation. When the level of education increases control of emotion decreases. Nurses with the longest work experience had fewer care difficulties among patients with cancer. There was a significant correlation between the level of empathy or empathetic tendency and ways of coping with oncological patients care problems.